A Review about Economic Policy 1991 in India: A comprehensive analysis of India's economic performance from 1991 to 2013 (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Since 1951, India has fully fledged like a planned economy. The very first couple of plans centered on development with strengthening of manufacturing sector and the manufacturing to develop the backbone of the Indian economy. Other primary aspects of planning were agriculture, employment generation, poverty alleviation, social development etc. In 1991, India saw itself fighting its most crucial economic and currency crisis ever, but after financial reforms and following the policy of LPG (Liberalization, Privatization, and Globalization) Indian economy performed very well. Then again because of global financial crisis in 2008 Indian economy again interrupted and starting another turbulent phase. This paper analysis Indian economy from 1991 2013.